Determine the Obesity as a Risk Factor for Gestational Diabetes Mellitus and Gestational Hypertension as Compared to Non-Obese Patients - Riaz, Samreen (International Journal of Pathology, 2021)
Introduction: Obesity has been recognized by the World Health Organization as a pandemic nutritional disorder which represents a rapidly growing threat to the health of populations of an increasing number of countries worldwide. Objectives: The objective was to determine the obesity as a risk factor for Gestational Diabetes Mellitus and Gestational Hypertension when compared with non-obese patients. Material & methods: A cohort study in which comparison of obese patients versus non-obese patients for developing gestational diabetes mellitus and gestational hypertension was done during November 2019 to October 2020. Results: The results of the current study reveals that mean BMI was as 27.86±4.21 in Group-1 and 26.33±3.87 years in Group-2. Comparison of risk factors (gestational diabetes mellitus) in both groups was done which reveals 15.33% (n=23) in Group-1 and 3.33% (n=6) in Group-2, relative risk shows 3.83, which is significant. Conclusions: The frequency of maternal complications is higher among obese pregnant females as compared to normal weight females.